Relative risk of tuberculosis in patients with rheumatic diseases managed with anti-tumour necrosis factor-alpha therapy: A nationwide cohort study - AKICI, AHMET (WILEY, 2019)
What is known and objective Anti-tumour necrosis factor-alpha (anti-TNF-alpha) therapy is known to raise the risk of granulomatous infections, leading to development of risk management strategies at national or global level. This study aimed to determine the relative risk (RR) of tuberculosis (TB) due to anti-TNF-alpha usage in patients with rheumatologic diseases (RDs) in a nationwide basis. Method This retrospective cohort study included patients with rheumatoid arthritis (RA), ankylosing spondylitis, juvenile idiopathic arthritis or psoriatic arthritis (PsA) that treated with or without anti-TNF-alpha agents, as registered in the national prescription information system between years 2013 and 2015. Two-year RR of TB after anti-TNF-alpha therapy initiation was calculated in this RD population, including main subgroups. Results and discussion The study cohort included 413 500 RD patients, where anti-TNF-alpha(+) arm (n = 2117) had mean age of 41.9 +/- 13.4 years and male distribution of 54.3%. Four patients among anti-TNF-alpha users developed TB compared to 128 patients in anti-TNF-alpha-naive group (189 vs 31 cases per 100 000 patients, respectively), yielding a 2-year RR of 6.07 (95% CI, 2.25-16.42) with an attributable risk of 0.16%. These RRs (95% CI), which were particularly pronounced, were 5.39 (1.69-7.17) in men, 6.12 (2.26-16.55) in adults, and 5.70 (1.41-23.08) in RA and 13.46 (1.58-114.40) in PsA patients. There was no difference between the anti-TNF-alpha users who developed and undeveloped TB regarding drug utilization characteristics, except significantly less immunosuppressive drug exposure in TB patients. What is new and conclusion This study is the first prescription-based nationwide study to suggest an elevated RR of TB in a comparably younger population with a broad spectrum of RDs managed with any approved anti-TNF-alpha drug in Turkey.
Keywords: anti-TNF-alpha; drug safety; rheumatologic disease; tuberculosis; LATENT TUBERCULOSIS; PSORIATIC-ARTHRITIS; FACTOR ANTAGONISTS; INFLIXIMAB; INFECTIONS; TRIALS